LARANGAN EKSPOR BIJIH NIKEL INDONESIA DIANTARA STABILITAS PERDAGANGAN INTERNASIONAL - Hanina Haddad; Helitha Novianty; Huala Adolf (Mimbar Hukum, 2022)
Abstract The Indonesian government through the Minister of Energy and Mineral Resources Regulation No. 11 of 2019 regarding the Second Amendment to the Ministry of Energy and Mineral Resources Regulation No. 25 of 2018 regarding Mineral and Coal Mining has decided to accelerate the implementation of nickel ore exports starting from January 1, 2020. This regulation is considered to violate the General Elimination of Quantitative Restriction in Article XI of the General Agreement in Tariffs and Trade (GATT) and is being sued by the European Union to the WTO DSB. This article analyzes the scope of Article XI of the GATT and the conformity of the regulation on the ban on the export of nickel ore with justification in the GATT regulatory framework. This article uses a normative juridical approach, with the research done by examining library materials and secondary data. This research is a descriptive-analytical study that analyzes legal instruments related to the issues discussed, to deliver a comprehensive and systematic comprehension of the scope and application of the Quantitative Restriction Principle. This article also shows DSB WTO interpretation on Quantitative Restriction cases is still considered narrow and overrides the goals and rights of a country. Abstrak Pemerintah Indonesia melalui Peraturan Menteri Energi dan Sumber Daya Mineral No. 11 Tahun 2019 tentang Perubahan kedua atas Peraturan Menteri Energi dan Sumber Daya Mineral No. 25 tahun 2018 tentang Pengusahaan Pertambangan dan Mineral Batubara (Permen ESDM 11/2019) memutuskan untuk memberhentikan kegiatan ekspor bijih nikel mulai dari tanggal 1 Januari 2020. Peraturan ini dianggap melanggar Prinsip Restriksi Kuantitatif dalam Pasal XI General Agreement on Tariffs and Trade (GATT) dan dituntut oleh Uni Eropa kepada Dispute Settlement Body World Trade Organization (DSB WTO). Artikel ini menganalisa mengenai ruang lingkup dari Pasal XI GATT dan kesesuaian regulasi larangan ekspor bijih nikel dengan justifikasi dalam kerangka peraturan GATT. Artikel ini menggunakan metode pendekatan yuridis normatif, yakni penelitian hukum yang dilakukan melalui penelitian bahan pustaka serta data sekunder. Penelitian ini bersifat deskriptif analitis yang menganalisa instrument-instrumen hukum terkait, untuk memberikan pemahaman secara menyeluruh dan sistematis terhadap ruang lingkup dan pemberlakuan Prinsip Restriksi Kuantitatif. Artikel ini juga menunjukan bahwa, interpretasi dari panel DSB WTO terhadap suatu kasus masih ternilai sempit dan mengesampingkan tujuan serta hak suatu negara.